Effects of Dietary Bacillus and Non-starch Polysaccharase on the Intestinal Microbiota and the Associated Changes on the Growth Performance, Intestinal Morphology, and Serum Antioxidant Profiles in Ducks - Peng, Simin; Wang, Xin; Wang, Yuyu; Lv, Tuo; Zhao, Haohan; Wang, Yanzhou; Zhu, Siyuan; Qiu, Huajiao; Zeng, Jianguo; Dai, Qiuzhong; Lin, Qian (Frontiers in Microbiology, 2021)
Given the of desirable results of using probiotics and enzyme preparations as feed supplements in poultry health. Here, the effects of Bacillus and Non-starch Polysaccharase (NSPase) on the growth performance, serum antioxidant profiles, and gut microbial communities of early-stage ducks were investigated. 400 Zhijiang ducks (similar in body weights and 1 d age) were selected and randomly divided into 4 groups. The feeding period was 28 days. Each group contained 10 replicates of 10 birds. Control group (Ⅰ) feed with basal diet, test groups Ⅱ to Ⅳ were respectively fed with 150 mg/kg NSPases, 25 mg/kg Bacillus probiotics, 150 mg/kg NSPases + 25 mg/kg Bacillus probiotics in basal diet. The results demonstrated that dietary Bacillus (25 mg/kg) increased average final weight, average daily gain (ADG) and decreased the malonaldehyde (MDA) in birds (P < 0.05). Dietary Bacillus (25 mg/kg) and NSPases+Bacillus (150 mg/kg+25 mg/kg) presented much higher glutathione (GSH) and activities of superoxide dismutase (SOD) in birds (P < 0.05). Additionally, as revealed by β-diversity indices and analysis of similarities, dietary NSPases+Bacillus could affect the ileum microbial abundances and diversities at the genera level (P < 0.05), but it had no effect on the caecum. 16S rRNA sequencing revealed that dietary Bacillus and NSPases+Bacillus increased the populations of Ruminococcaceae genera in the cecum (P < 0.05), and S24-7_group and Lactobacillus genera in the ileum (P < 0.05). However, dietary NSPases and Bacillus alone and in combination could significantly decreased the content of Bacteroides in ileum (P < 0.05). According to Spearman correlation analysis, 7 ileum bacterial microbiome (S24-7 group, Lactobacillus, Subgroup 2, Subgroup 1, Kitasatospora, Candidatus Solibacter and Akkermansia) were significantly positive correlated with SOD (P < 0.05). In conclusion, Bacillus (25 mg/kg) and NSPases (150 mg/kg) included in the diet could efficiently enhance the growth performance by altered gut microbiota composition at genera level and antioxidant indices of ducks.